2006
DOI: 10.1038/sj.cgt.7700953
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional targeting of adenovirus vectors with the squamous cell carcinoma-specific antigen-2 promoter for selective apoptosis induction in lung cancer

Abstract: Squamous cell carcinoma antigens SCCA1 and SCCA2 are highly homologous serine proteinase inhibitors which have been widely utilized as serological markers for squamous cell cancers, but it has recently been demonstrated that only SCCA2 is truly specific for certain forms of lung cancer. Using a construct containing the 5 0 -flanking region of the SCCA2 gene between À460 and þ 0 bp and the luciferase reporter gene, SCCA2 promoter activity was detected in SCCA2-producing SCC cell lines (LK-2, LC-1), but not in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…SLPI promoter selected as tissue-specific promoter in Hep-2 laryngeal carcinoma cells According to published literatures, three fragments of SLPI promoter (SLPIa, SLPIb and SLPIc ), 11 SCCA2 (À460 to 0) 5 and survivin (À1471 to À36) 12 genes were cloned by PCR and evaluated for their transcription activity. Dual-luciferase reporter assay showed that promoter SLPIb exhibited the highest transcription activity in Hep-2 cells among the promoters evaluated (Po0.05, one-way analysis of variance test) ( Table 2), and also exhibited specific transcription activity in Hep-2 cells when compared with that in either HUVEC or MG-63 cells, with approximately 37-fold and 17-fold differences, respectively (Figure 1), and was therefore selected as the tissue-specific promoter in Hep-2 laryngeal carcinoma cells in subsequent recombinant adenoviral vector construction.…”
Section: Resultsmentioning
confidence: 99%
“…SLPI promoter selected as tissue-specific promoter in Hep-2 laryngeal carcinoma cells According to published literatures, three fragments of SLPI promoter (SLPIa, SLPIb and SLPIc ), 11 SCCA2 (À460 to 0) 5 and survivin (À1471 to À36) 12 genes were cloned by PCR and evaluated for their transcription activity. Dual-luciferase reporter assay showed that promoter SLPIb exhibited the highest transcription activity in Hep-2 cells among the promoters evaluated (Po0.05, one-way analysis of variance test) ( Table 2), and also exhibited specific transcription activity in Hep-2 cells when compared with that in either HUVEC or MG-63 cells, with approximately 37-fold and 17-fold differences, respectively (Figure 1), and was therefore selected as the tissue-specific promoter in Hep-2 laryngeal carcinoma cells in subsequent recombinant adenoviral vector construction.…”
Section: Resultsmentioning
confidence: 99%
“…One way to circumvent the non-specific delivery is to develop a strong cancer-specific expression vector. Most of the identified lung cancer-specific promoters exhibit a high level of lung cancer specificity but are still much weaker than the CMV promoter (Chen et al , 2004; Fukazawa et al , 2007; Oshikiri et al , 2006). To overcome this issue, we have established a specific promoter amplification system, called “VISA” (VP16-GAL4-WPRE integrated systemic amplifier) system (Xie et al , 2007) to significantly amplify the cancer-specific promoter activity to a comparable level to CMV in cancer cells while still retaining low promoter activity in normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…SCCA2 promoter has been used to control proapoptotic gene expression by adenoviral vectors for selective induction of apoptosis in SCCA2-expressing lung cancer cells. 30 As the majority (up to 80%) of cervical cancers overexpress SCC, it is reasonable to use this modality for treating cervical cancer clinically. To our knowledge, this is the first report to use the SCCA2 promoter to transcriptionally drive the replication of an oncolytic adenovirus specifically in metastatic cervical tumors.…”
Section: Discussionmentioning
confidence: 99%
“…At nucleotide position À50, the A residue in SCCA2 is replaced by a G residue in SCCA1, and this appears to be responsible for the difference in transcriptional activities of the two promoters. 30 The complete SCCA2 gene locus has been cloned and its putative promoter region has been analyzed. The SCCA2 core promoter region exhibited a higher promoter activity in SCCA2-producing SKGIIIa than in nonproducing SK-OV-3 or K42 cells.…”
Section: Discussionmentioning
confidence: 99%